IMPLEMENTASI KEBIJAKAN PENDIRIAN MINIMARKET/ SWALAYAN dan DAMPAK terhadap WARUNG-WARUNG TRADISIONAL di KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU - NURHASANAH " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Abstract: Policy Implementation of Established Minimarket/ Swalayan andImpact Toward Traditional Small Shops in Kelurahan Simpang BaruKecamatan Tampan Kota Pekanbaru. This research aimed to know how Policyimplementation established minimarket/ swalayan by Dinas Perindustrian danPerdagangan and Badan Pelayanan Terpadu and also to knew how the impact ofesablished minimarket/ swalayan toward traditional small shops. This research aredescriptive qualitative where data tabulation was done with tringulation technique.The result of research showed policy implementation established minimarket/swalayan by department of industry and commercial pekanbaru city and BadanPelayanan Terpadu was not good. This matter proved that found minimarket/swalayan which existenced near traditional small shops and also did not haveoperational license with the result that could cause negative impact towardtraditional small shops in Kelurahan Simpang Baru Kecamatan Tampan KotaPekanbaru that was decreasing sale and also there are few traditional small shopsowner could not compete and change profession. As to suggestion in this researchwas to increased coordination in the management of operational license and alsopresent a harsh punishment toward minimarket/ swalayan owner who broke theregulations. Implementasi, kebijakan, Dampak